Access rights, capacities and benefits in small-scale fisheries: Insights from the Pacific Coast of Canada. (August 2021) - Bennett, Nathan J.; Ban, Natalie C.; Schuhbauer, Anna; Splichalova, Dacotah-Victoria; Eadie, Megan; Vandeborne, Kiera; McIsaac, Jim; Angel, Eric; Charleson, Joshua; Gavenus, Erika R.; Harper, Sarah; Satterfield, Terre; et al.
Abstract: Small-scale fisheries depend on availability of and access to resources. Yet research on access – the combination of rights and capacities that enable fishers to benefit from available resources – has been limited compared to research on availability in Canadian fisheries. We surveyed 118 independent fishers in British Columbia, Canada to understand access rights (harvesting, entrance, transferability, security and protection), capacities (physical, human, social, cultural, political and financial assets), economic benefits from fishing, and actions to maintain or increase access. Participants generally perceived: strengths in physical, human and cultural assets; varied status in social and financial assets; and weaknesses in political assets. Access rights were generally perceived as poor with the exception of transfer rights. We employed modeling approaches to understand demographic characteristics of participants with higher rights and capacity, and which factors predicted feasibility and economic benefits of fishing. Higher perceived rights and capacities were both predicted by whether the participant self-identified as Indigenous. Higher feasibility of fishing was associated with higher political and financial assets, higher rights, being non-Indigenous, rural residence, and higher incomes. Higher income from fishing was predicted by higher financial assets and being non-Indigenous. Qualitative results showed participants maintain or gain access through: preparation; non-political networking; political advocacy; augmenting licenses or quota; or, diversification and intensification of fishing activities. Yet, many participants reported feeling powerless. Our research emphasizes the need to address access in fisheries management. Our novel conceptualization and mixed methods approach to study access rights and capacities can be adapted and applied elsewhere. Highlights: The viability of small-scale fisheries livelihoods depends on both availability of and access to resources. Access refers to the combination of rights and capacities that enable fishers to benefit from available resources. We surveyed 118 small-scale fishers on the Pacific Coast of Canada to understand access rights, capacities, and benefits. Fishers perceived strong physical, human and cultural assets, varied financial assets, and weak political assets and rights. Our novel and mixed methods approach to study access rights and capacities might be adapted and applied elsewhere.